2015
DOI: 10.1007/s00442-015-3401-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in body condition and order of arrival influence competitive ability and survival in a coral reef fish

Abstract: Trade-offs between traits that influence an individual's competitive ability are important in determining community assembly and coexistence of individuals sharing the same resources. Populations of coral reef fish are structurally complex, so it is important to understand how these populations are shaped as a result of an individual's suite of traits and those of its competitors. We conducted a 2 × 2 factorial field experiment that manipulated body condition (high or low, manipulated through a feeding regime)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 70 publications
0
25
0
Order By: Relevance
“…Fish that developed entirely at elevated temperatures were smaller than fish from all other exposure duration treatments and the control group. Smaller body size is ecologically important in juvenile fish as it typically increases the risk of predation and reduces competitive ability (Poulos and McCormick, 2015;Goatley and Bellwood, 2016;Sogard, 1997). Reduced body size is likely due to increased energy costs for maintenance activities at higher temperatures (Munday et al, 2008;Pörtner and Knust, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fish that developed entirely at elevated temperatures were smaller than fish from all other exposure duration treatments and the control group. Smaller body size is ecologically important in juvenile fish as it typically increases the risk of predation and reduces competitive ability (Poulos and McCormick, 2015;Goatley and Bellwood, 2016;Sogard, 1997). Reduced body size is likely due to increased energy costs for maintenance activities at higher temperatures (Munday et al, 2008;Pörtner and Knust, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…plasticity) could be disentangled from the effect of the final temperature of each treatment at 108 days (Schulte et al, 2011). We also measured body size, which is a key fitness-related trait in juvenile fishes that links to competitive ability and predation risk (Sogard, 1997;Poulos and McCormick, 2015;Goatley and Bellwood, 2016). Reduced growth rates and smaller body size with increased warming is a commonly observed trend in fishes (Cheung et al, 2013;Munday et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies across multiple taxa have demonstrated that individuals face a decline in the survival probability of offspring as the breeding season progresses (mammals: e.g., Morris, ; insects: e.g., Johansson & Rowe, , reptiles: e.g., Doody, Gorges, & Young, , fish: e.g., Poulos & McCormick, , and birds: e.g., Rowe et al., ; Bêty, Gauthier, & Giroux, ). For many species breeding in seasonal environments, a critical trade‐off occurs between the delay in timing of reproduction in favour of increased body condition and the ability to increase investment in reproduction, against this declining survival probability of the resulting offspring (Bêty et al., ; Drent & Daan, ; Lepage, Gauthier, & Menu, ; Morris, ; Rowe & Ludwig, ; Rowe et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The model predicts that individuals arriving from migration to the breeding grounds earlier and in better body condition (i.e., higher body mass or size-corrected body mass) have the potential to acquire the local resources they need to fuel re-production earlier and therefore initiate reproduction earlier, a key fitness-related parameter in many avian species (Drent and Daan 1980;Rowe et al 1994;Lepage et al 2000;Bêty et al 2003;Descamps et al 2011). Although applied in insect (Johansson and Rowe 1999), mammal (Dobson and Michner 1995;Marrow et al 1996;Morris 1998), reptile (Doughty 1996;Doody et al 2003), and fish (Cargnelli and Neff 2006;Poulos and McCormick 2015) systems, the model's ultimate goal is to examine the mechanisms behind the well-known seasonal decline in clutch size in many avian species, where earlier laying dates should be associated with greater investment in reproduction (i.e., clutch size; Drent and Daan 1980;Rowe et al 1994;Bêty et al 2003;Descamps et al 2011). Independent of arrival date and condition, Rowe et al (1994) also made a second set of important predictions that, to date, have received far less attention in the literature.…”
Section: Introductionmentioning
confidence: 99%